15 ways to boost staff’s morale - Suriya Kumar, Sinnadurai (Pejabat Naib Canselor, 2009)
Employees’ spirits can easily fall if their day-to-day responsibilities are monotonous or if they don’t feel valued by their superiors. Over time, this can translate into an unmotivated and unproductive staff. Therefore, it is important to make sure that employees are interested in and appreciated for their work. Use these 15 tips to help improve employees’ morale and boost productivity within your organisation.